In Situ Monitoring of Particle Formation with Spectroscopic and Analytical Techniques Under Solvothermal Conditions. Issue 5 (9th April 2020) - Embrechts, Heidemarie; Hartmann, Martin; Peukert, Wolfgang; Distaso, Monica
Abstract: The formation of multifunctional materials involves various simultaneous and closely entangled physicochemical processes including nucleation, growth, aggregation, and in some cases also growth by oriented aggregation. These elementary particle formation processes occur in broad size ranges from the molecular to micrometer level and time scales ranging from seconds to hours. This contribution demonstrates that the in situ monitoring of reaction mixtures and dispersions with several simultaneous analytical and spectroscopic techniques is an effective and widely applicable strategy to achieve an in‐depth understanding of the formation of complex particulate structures and to move towards the rational design of materials. Abstract : A reactor equipped with multiple and simultaneous analytical and spectroscopic techniques was designed to unravel the fundamentals of solid formation under hydro‐ and solvothermal conditions. An overview of the results obtained with the metal‐organic framework MIL‐53(Al), ZnO mesocrystals, and carbon dots is provided. This strategy paves the way for the rational design of a wide range of material systems.